Islamic Capital Market Investment Alternatives Facing the 2024 Election Year - Fatkhurrozi, Tanto (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2024)
This research aims to determine alternative investment instruments that are relevant in the Islamic capital market in the 2024 election period. This research uses a library research method, which involves collecting relevant data or library materials beforehand. The data source in this research is secondary, meaning that the data is obtained from other sources such as documents, books, and related references, not from primary sources. The results of this research are that the development of investment in the Islamic capital market during the election period in the previous year experienced a good increase. from stock instruments, mutual funds, and sharia shares and the recommended investment, namely Sukuk, is considered an instrument that is relatively unaffected because it has a guarantee from the law. Sharia mutual funds show positive long-term growth potential, especially for mutual funds that focus on shares. This performance is influenced by the momentum of the underlying stock. In this context, investors in the Islamic stock market are advised not to make hasty investment decisions. The analysis shows that the infrastructure sector and the information technology (IT) sector have a significant positive influence.